Ivermectin: Potential Role as Repurposed Drug for COVID-19 - Dixit, Alok (Malays J Med Sci, 2020)
Severe acute respiratory illness caused by 2019 novel coronavirus (2019-nCoV), officially named severe acute respiratory syndrome coronavirus (SARS-CoV-2) in late December 2019 is an extremely communicable disease. World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) as a pandemic as it has spread to at least 200 countries in a short span of time. Being a new disease there is lack of information about pathogenesis and proliferation pathways of this new coronavirus. Currently there is no effective treatment for coronavirus infection; major effort is to develop vaccine against the virus and development of therapeutic drugs for the disease. The development of genome-based vaccine and therapeutic antibodies require thorough testing for safety and will be available after some time. In the meanwhile, the available practical approach is to repurpose existing therapeutic agents, with proven safety record as a rapid response measure for the current pandemic. Here we discuss the presently used repurposed drugs for COVID-19 and the potential for ivermectin (IVM) to be used as a therapeutic option in COVID-19.